find (g*f)(3)
f(x)= 3x-2
g(x)=x2
![find gf3 fx 3x2 gxx2 class=](https://us-static.z-dn.net/files/d43/4bf408fbcd509331234931261565c4b6.png)
Answer:
C
Step-by-step explanation:
( g o f)( 3) means to substitute the value x=3 after substituting f(x) into g(x).
[tex](3x-2)^2\\(3(3)-2)^2\\(9-2)^2\\7^2\\49[/tex]
Answer:
49 choice C is the correct solution
Step-by-step explanation:
The composite function, (g o f) simply means we substitute the function f(x) in place of x in the function g(x). since g(x) =x^2, (g o f) =(f(x))^2 = (3x-2)^2. The final step is to substitute x=3 in this expression which yields 49